Efficient trifluoromethylation of C(sp(2))-H functionalized alpha-oxoketene dithioacetals: a route to the regioselective synthesis of functionalized trifluoromethylated pyrazoles - Sharma, N.; Kumari, N.; Chundawat, T. S.; Kumar, S.; Bhagat, S. (RSC Advances, 2017)
An operationally simple approach for the regioselective construction of diversely substituted trifluoromethylated pyrazoles via nucleophilic trifluoromethylation of iodo-substituted alpha-oxoketene dithioacetals is described. X-ray crystallographic studies confirmed the trifluoromethylation as well as formation of a regioselective cyclized product. Furthermore, trifluoromethylated pyrazoles bearing thiomethyl groups may allow further functionalization and are of considerable interest in medicinal chemistry.